Infection of the Stable Fly, Stomoxys calcitrans, L. 1758 (Diptera: Muscidae) by the Entomopathogenic Fungi Metarhizium anisopliae (Hypocreales: Clavicipitaceae) Negatively Affects Its Survival, Feeding Propensity, Fecundity, Fertility, and Fitness Parameters - Baleba, Steve B. S.; Agbessenou, Ayaovi; Getahun, Merid N.; Akutse, Komivi S.; Subramanian, Sevgan; Masiga, Daniel (Frontiers in Fungal Biology, 2021)
Entomopathogenic fungi can cause substantial mortality in harmful insects. Before killing the insect, these pathogens start by negatively affecting the biological parameters of the host. Prior to our study, the information about how fungal exposure affects the biological parameters of the stable fly, Stomoxys calcitrans was still elusive. Therefore, we aimed to assess the infection of S. calcitrans with some Metarhizium anisopliae strains, and their impact on feeding, fecundity, fertility and other life-history traits of this fly. Among the 11 M. anisopliae strains screened, we identified ICIPE 30 as the most virulent strain against S. calcitrans. We observed that the infectivity of this strain was sex and age-dependent. Infected male S. calcitrans died earlier than their counterpart females. Older infected S. calcitrans died faster than infected young ones. Also, male and female S. calcitrans successfully transmitted ICIPE 30 conidia to their mates. We demonstrated that infection by ICIPE 30 extended the feeding time of S. calcitrans and consequently reduced the feeding probability of the fly and the amount of blood taken. Using a dual test oviposition bioassay, we determined that uninfected gravid female S. calcitrans avoided laying eggs on substrates amended with ICIPE 30 conidia. We showed that these conidia could lower the hatchability of the eggs deposited by gravid females. Using, a no-choice test, we showed that gravid female S. calcitrans infected with ICIPE 30 laid fewer eggs than uninfected females and those eggs hatched less. Using 11 strains of M. anisopliae and four high concentrations of ICIPE 30 conidia, we verified that S. calcitrans larvae were not susceptible to fungal infection. Further, we showed that though these larvae were tolerant to fungal infection, there was a significant effect on their fitness, with contaminated larvae having a small bodyweight coupled with longer developmental time as compared to uncontaminated larvae. Our study provides detailed information on how fungal infection affects the biology of S. calcitrans and the potential of using M. anisopliae ICIPE 30 as a biopesticide to reduce the fly population. Such knowledge can assist in developing fungal-based control strategies against this harmful fly.